Candy draws a square design with a side length of x inches for the window at the pet shop. She takes the design to the printer and asks for a sign that has an area of 16x2 – 40x + 25 square inches. What is the side length, in inches, of the pet shop sign?
Answer:
the length of the sign is inches
Step-by-step explanation:
Given
Area of the square of design =
First we find the roots of equation
The roots of the quadratic equation are given by
where
That is, the factors of the polynomial are and .
So, Area of the square design = =
Area of a square = Length^2
Thus, the length of the sign is inches
Answer:
Step-by-step explanation:
1. So there is two bread options but let's ignore that due every option being the same for both bread options.
2. So if you look there are three meat options meaning there is a one in three chance logical chance someone picks turkey (note when I say logical I mean that doesn't mean that this will be true in real life) and there is a one in two logical chance someone picks Swiss cheese.
3. So with a one in three chance logical meat option and a one two chance cheese option and.
4. Now knowing this it is simple math at this point as simple as x
5. 1 x 1 = 1 and 3 x 2 = 6
6. leading to
Answer:
At 7% $54,000
At 9% $156,000
Step-by-step explanation:
Let x be the amount invested at 7%, Then 2x + 48000 will be the amount invested at 9%
We know that:
7% = 0.07 & 9% = 0.09
So we can write the interest equation as follows:
0.07x + 0.09 (2x + 48000) = 17820
0.07x + 0.18x + 4320 = 17820
0.25x + 4320 = 17820
Subtracting 4320 from both sides of the equation we get:
0.25x = 17820 - 4320
0.25x = 13500
Dividing both sides of the equation by 0.25 we get:
x = 13500 / 0.25
x = $54,000 invested at 7%
&
2 x 54000 + 48000
= $156,000 invested at 9%
Hence the amount invested at 7% is $54,000.
& the amount invested at 9% is $156,000.
The zeroes ( where the graph cuts the x axis) ar (-2,0) AND (2,0)
tHE FACTOrIAL FORM IS (x - 2)(x + 2)
Its B
Tan²( θ ) - (1 + √3) tan (θ) + √3 = 0
tan²( θ ) - (tan (θ) + √3 tan (θ)) + √3 = 0
tan²( θ ) - tan (θ) - √3 tan (θ) + √3 = 0
tan( θ ) ( tan (θ) - 1) - √3 ( tan (θ) - 1 ) = 0
( tan( θ ) - 1 ) ( tan( θ ) - √3 ) = 0
tan( θ ) - 1 = 0
θ = π/₄
tan( θ ) - √3 = 0
θ = π/₃
so θ = π/₄ and θ = π/₃